A retrospective study of positive and negative determinants of gamete storage in transgender and gender-diverse patients. Issue 1 (11th November 2020) - Rogers, Chloë; Webberley, Mike; Mateescu, Roxana; El Rakhawy, Yasmeen; Daly-Gourdialsing, Anaïs; Webberley, Helen
Abstract: Background: GenderGP is a novel, online telemedicine service for transgender and gender-diverse individuals. As part of the service, people are offered fertility counseling in regard to gamete storage. Aims: This study aims to formally categorize the reasons that transgender and gender-diverse people do and not store gametes prior to hormonal treatments. We hope to use this data and subsequent research to inform healthcare policy, improve the healthcare experience for transgender and gender-diverse people, and inform legislation for permanent change in UK healthcare. Methods: Data sets (electronic medical records) from June 2015 – April 2020 were derived from the GenderGP patient database. All patients starting treatment with GenderGP and undergoing routine fertility counseling were included in the study. Results: Of 3667 patients aged 10–85, 2722 (74.2%) were aged 18–45. 151 (5.4%) patients stored gametes. 678 (18.5%) patients wanted to store: 268 (39.5%) could not afford gamete storage, 84 (12.4%) had no local services, 307 (45.3%) did not want to delay hormone treatment. 2085 patients did not want to undertake gamete storage, 480 (23.0%) hoped to adopt, 1605 (77.1%) did not want children. All ages showed similar patterns. Discussion: Financial barriers mean many transgender and gender-diverse people cannot access fertility healthcare. Many participants suffered low self-esteem and struggled to envisage an accepting healthcare system, making them less likely to seek advice. Many patients favored adoption over gamete storage. Younger patients (<18) often had very definite views on gamete storage. Many older patients without children would consider gamete storage and adoption, once their transition is complete.